2022
DOI: 10.1042/bsr20220583
|View full text |Cite
|
Sign up to set email alerts
|

A potential oral microbiome signature associated with coronary artery disease in Tunisia

Abstract: The coronary artery disease is a chronic inflammatory disease involving genetic as well as environmental factors. Recent evidence suggests that the oral microbiome has a significant role in triggering atherosclerosis. The present study assessed the oral microbiome composition variation between coronary patients and healthy subjects in order to identify a potential pathogenic signature associated with coronary artery disease (CAD). We performed metagenomic profiling of salivary microbiomes by 16S rRNA next-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Veillonella could be found in atherosclerosis plaque and associated with cholesterol levels 43 . In addition, Veillonella is high relative abundance in CAD patients 35,44 . These ndings suggested that the differences in bacterial abundance between the three groups may be linked to the progression of CAD and lipid metabolism in dyslipidemia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Veillonella could be found in atherosclerosis plaque and associated with cholesterol levels 43 . In addition, Veillonella is high relative abundance in CAD patients 35,44 . These ndings suggested that the differences in bacterial abundance between the three groups may be linked to the progression of CAD and lipid metabolism in dyslipidemia patients.…”
Section: Discussionmentioning
confidence: 99%
“…CVD refer to circulatory system disorders, including strokes and myocardial infarction. Environmental and genetic factors also contribute to coronary artery disease (CAD) as a chronic inflammatory condition [59]. Age raises the chance of CVD as a standalone risk factor, especially if other comorbidities such as frailty, diabetes, and obesity accompany it [110].…”
Section: Cvdmentioning
confidence: 99%
“…Higher levels of the phyla Actinobacteria and lower levels of the Bacteroidetes were observed in patients with ACVD [63]. Bouzid et al [59] stated that the same global core oral microbiome represents oral microbial communities in healthy individuals and patients. They found the most prevalent phyla to include Actinobacteria, Firmicutes, Bacteroidetes, Fusobacteria, TM7, and Proteobacteria.…”
Section: Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral microbiome is an ecosystem composed of many different microorganisms. Bouzid et al [19] conducted a metagenomic study of the saliva microbiome using next-generation 16S ribosomal RNA (rRNA) sequencing techniques. They used oral microbiome profiling among 20 people with CAD and among 10 people without atherosclerotic plaques in the carotid arteries, but after stroke or myocardial infarction.…”
Section: Oral Dysbiosismentioning
confidence: 99%